CCPA Accreditation of Counsellor Education Programs in Canada: An Historical Perspective - Robertson, Sharon E.; Borgen, William (Canadian Journal of Counselling and Psychotherapy, 2016)
Since the 1970s, the Canadian Counselling and Psychotherapy Association has promoted the development of guidelines and standards for the education and training of counsellors in Canada. This article outlines the evolution of this process from early discussions and initiatives into formal procedures and standards for accreditation of counsellor education programs at the master’s level and the creation of the Council on Accreditation of Counsellor Education Programs (CACEP). The activities of CACEP are described, the significance of CACEP accreditation is explained, and suggestions for the further development of CACEP accreditation of counsellor education programs in Canada are provided.